The Murchison Widefield Array Commissioning Survey: A Low-Frequency Catalogue of 14 110 Compact Radio Sources over 6 100 Square Degrees - Hurley-Walker, Natasha; Morgan, John; Wayth, Randall; Hancock, Paul; Bell, M.; BERNARDI, G.; Bhat, Ramesh; Briggs, F.; Deshpande, A.; Ewall-Wice, A.; Feng, L.; Hazelton, B.; et al. (Cambridge University Press, 2014)
We present the results of an approximately 6 100 deg2 104–196 MHz radio sky survey performed with the Murchison Widefield Array during instrument commissioning between 2012 September and 2012 December: theMWACS. The data were taken as meridian drift scans with two different 32-antenna sub-arrays that were available during the commissioning period. The survey covers approximately 20.5 h< RA < 8.5 h, −58◦ < Dec < −14◦over three frequency bands centredon 119, 150 and 180 MHz, with image resolutions of 6–3 arcmin. The catalogue has 3 arcmin angular resolution and a typical noise level of 40 mJy beam−1, with reduced sensitivity near the field boundaries and bright sources. We describe the data reduction strategy, based upon mosaicked snapshots, flux density calibration, and source-finding method. We present a catalogue of flux density and spectral index measurements for 14 110 sources, extracted from the mosaic, 1 247 of which are sub-components of complexes of sources.